(untitled) (The Pretoria Student Law Review, 2025)
The advent of crypto assets has led to creative alternative ways of raising capital for emerging businesses through token sales, aptly termed Initial Coin Offerings or ICOs. The crypto asset market has experienced a period of high market growth in the past decade due to ICOs — a relatively new phenomenon in the financial markets — which has seen investors invest their hard-earned capital despite the information asymmetry and associated risks. The lack of regulation in ICOs and crypto assets, in general, has prompted regulators to take steps towards regulation. This submission explores how South Africa proposes to regulate ICOs and provides a comparison with the European Union’s approach towards regulating ICOs by paying specific attention to the governmental papers published in the respective jurisdictions.